Assessment of Family Planning Counseling Provided for Postpartum Women and Associated Factors. (27th January 2020) - Abdulreshid, Munit; Dadi, Hailemichael B.
Abstract : Background . Good quality family planning counseling particularly in the postpartum period is paramount to contraception adoption and continuation; it is also paramount in the reduction of maternal as well as infant morbidity and mortality. Objective . Assess the level of family planning counseling provided for women in their immediate postpartum period in the labor ward at Saint Paul's Hospital in 2019. Method . An institution-based cross-sectional study was conducted from February to March of 2019 among women in the labor ward. A face-to-face exit interview was conducted with 209 randomly selected women. A structured pretested questionnaire was used to assess the level of family planning counseling provided. Bivariate logistic regression was used to test for statistical association. Results . Only 28.2% of the counseling sessions were adequate. Most (58.9%) of the counseling sessions did not maintain the privacy of the client. In 67.9% of the sessions, the counselor did not ask the concern of the client regarding the use of modern family planning methods and 74.2% of the clients were not told about the possible side effects of a method. Clients with no formal education (OR = 2.52, 95 % CI = 1.1 ‐ 3.3 ) and those with only primary level education (OR = 1.22, 95 % CI = 1.04 ‐ 3.02 ) were more likely to have had inadequate counseling. Conclusion . The level of family planning counseling was inadequate. The study indicated the need to provide training for service providers on family planning counseling with the existing standard frameworks but also in consideration of the sociodemographic background of the client, particularly their educational status.